ON THE INFLUENCE OF CONTINUOUS MEDIUM ON THE GRAVITATIONAL FIELD OF MASS - VDOVYNA, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The system of the differential equations of the static (gravitational, electric, magnetic) field in the heterogeneous continuous mediums, which allows to obtain a new solutions of the direct and inverse problems of the geopotential fields, considering the influence of heterogeneity of the studied models is proposed. This model of the static vector field is described by a system of differential equations of the first and second orders. The equations includes the characteristics of the field (tension, potential) and physical characteristics of the environments in which this field exists and which influence to the magnitude of the field.